Seipin—still a mysterious protein? - Salo, Veijo T. (Frontiers in Cell and Developmental Biology, 2023)
Cells store excess energy in the form of lipid droplets (LDs), a specialized sub-compartment of the endoplasmic reticulum (ER) network. The lipodystrophy protein seipin is a key player in LD biogenesis and ER-LD contact site maintenance. Recent structural and in silico studies have started to shed light on the molecular function of seipin as a LD nucleator in early LD biogenesis, whilst new cell biological work implies a role for seipin in ER-mitochondria contact sites and calcium metabolism. In this minireview, I discuss recent insights into the molecular function of seipin.